The MillennialÔÇÖs Role in Improving the Community Welfare - Sari, Irma; Prayoga, Andhika Gilang; Fadri, Zainal; Hakim, Arif Rahman (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2022)
The teenager nowadays takes the advantage of the time for things that do not provide a good feed back for himself, his family and the environment, this is a necessary thing to do coaching to the teenager, So as to be able to manage its time on useful things, what's more, the state of the world always strives to improve the quality of life of people, both regional, national and international. The global community deserves justice, protection, rights as citizens also their welfare. In an effort toimprove welfare is certainly not an easy thing, is a big PR for each government. The stability of the adolescent community the stability of the adolescent community which is adjusted to the needs of the community itself, besides that of course it can also provide the assistance to the community itself. Managing every potential that the community has, the tampa area decrypts the rights of one and the other. So that, it is necessary for strategic things to be done in improving the welfare of the community so that the community can be encapsulated according to its needs. In this sophistication and technology, many things can be facilitated especially the existence of millennials who should also care about the environment, social and so on, in addition to the role of millennials, of course, the role of the government cannot also be separated, because this is a very big driving factor in crucial matters related to society. Because if you talk about the community, it is divided into several categories, City Communities and Village Communities, Non-Akedemic Communities and Academic Communities. Community welfare is certainly how to try to overcome social problems or problems that occur in the society. So that it is necessary to do this to be done research in the hope of a solution so that the solution can be solved these problems.